To find the solution to the system of equations given by:
- \( y = -2x - 4 \)
- \( y = 2x + 4 \)
we can set the two equations equal to each other since they are both equal to \( y \):
\[ -2x - 4 = 2x + 4 \]
Now, let's solve for \( x \):
- Add \( 2x \) to both sides:
\[ -4 = 4x + 4 \]
- Subtract \( 4 \) from both sides:
\[ -8 = 4x \]
- Divide both sides by \( 4 \):
\[ x = -2 \]
Now that we have \( x \), we can substitute it back into either of the original equations to find \( y \). Using the second equation:
\[ y = 2(-2) + 4 \]
\[ y = -4 + 4 = 0 \]
So the solution to the system of equations is:
\[ (x, y) = (-2, 0) \]
The coordinates of the solution are:
\[ \boxed{(-2, 0)} \]